Fenomena Kesurupan Dalam Persepsi Psikolog Dan Peruqyah - Syarifah Irkani (Faculty of Ushuluddin and Humanities, 2018)
This study aims to compare the perceptions of psychologists and who do people ruqyah to trans possession phenomena. This research is a comparative descriptive study using a qualitative approach. The subjects of this study amounted to 6 people consisting of 3 people who work as psychologists and 3 people who work as who do people ruqyah in the Pondok Sehat Al-Wahida. Data collection techniques used are interviews, observation, and documentation. Analysis of the data used with descriptive-comparative methods.Based on the results of the research can be concluded that there are differences and similarities of perceptions of psychologists and people who do ruqyah in viewing at the trance phenomenon in the city of Banjarmasin. The difference between the perception of psychologists and people who do ruqyah in viewing the phenomenon of trance is that psychologists view the phenomenon of possession using psychological theory, while peruqyah views the phenomenon of possession using Islamic studies so that treatment given by psychologists and people who do ruqyah has this difference in accordance with their scientific competencies. As for the similarities between the perception of psychologists and people who the ruqyah in viewing at the phenomenon of possession can be caused by psychological problems but they also believe in Islamic studies can be caused by a genie that penetrates the body,